Impact of monetary methods of economic regulation on fair pricing of shares in the Russian stock market - M. V. Kulikov (Вестник университета)
In the article, the author analyzes the Russian stock market, estimates the fair value of shares of domestic issuers and examines the impact on financial assets of the measures taken by the Central Bank of the Russian Federation within the framework of monetary policy. The fair value of securities is calculated on the basis of a constant dividend growth rate model, where the required return on equity is determined using the CAPM model. The results of the author’s comparative analysis of the fair value and market price of shares of Russian corporations show that securities on the Russian stock market are significantly undervalued. To eliminate the imbalances that have arisen in the financial market, the author suggests that the Central Bank of the Russian Federation implement a softer monetary policy, thus affecting the development of the domestic stock market and increasing the attractiveness of investments in securities of Russian corporations.